2018
DOI: 10.1111/jai.13739
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of a Gobiid fish Oxyurichthys tentacularis (Valenciennes, 1837) inhabiting Ashtamudi Lake, S. India

Abstract: Reproductive traits of Oxyurichthys tentacularis, a most demanded fish in Ashtamudi Lake, S. India were studied from samples collected using gill net, cast net and dip net during 2013–2015. Sexes were separated by observing the urogenital papilla in males and the gonads. Five maturity stages were identified by examining the gonads. Though advanced maturity stages were encountered throughout the year, higher preponderance of ripe gonads was discernible during August to November and February to April. Gonadosoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The fecundity of various species has been described in many studies as being linear as an allometric function of standard/total length and body weight (Ahamed, Saha, Ahmed, & Hossain, 2018;Barzotto & Mateus, 2016;Mohan, Harikrishnan, & Williams, 2018). There is also a linear relationship between gonad mass (Barzotto & Mateus, 2016) and ovary weight (Mohan et al, 2018). Similarly, the present study also indicated a greater body length and weight correlate well with the higher fecundity of A. labiatus in Lake Sentani.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The fecundity of various species has been described in many studies as being linear as an allometric function of standard/total length and body weight (Ahamed, Saha, Ahmed, & Hossain, 2018;Barzotto & Mateus, 2016;Mohan, Harikrishnan, & Williams, 2018). There is also a linear relationship between gonad mass (Barzotto & Mateus, 2016) and ovary weight (Mohan et al, 2018). Similarly, the present study also indicated a greater body length and weight correlate well with the higher fecundity of A. labiatus in Lake Sentani.…”
Section: Discussionsupporting
confidence: 75%
“…labiatus and its sympatric species (A. citrinellus) from other places in Indonesia (Adjie et al, 2011;Tampubolon et al, 2015). The fecundity of various species has been described in many studies as being linear as an allometric function of standard/total length and body weight (Ahamed, Saha, Ahmed, & Hossain, 2018;Barzotto & Mateus, 2016;Mohan, Harikrishnan, & Williams, 2018). There is also a linear relationship between gonad mass (Barzotto & Mateus, 2016) and ovary weight (Mohan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of gonad maturity can be used as an estimate of the reproductive status of fish. It is not yet known for certain the technical nature of sex change, but it is estimated from the size of male fish which is larger than female fish (Remya Mohan et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This comparison suggested that the data set was distributed around the model, covering all the size classes. Whether this condition was observed or not could have caused misspecifications in the models, providing bias in estimates with evident poor fit [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%